CONIFER FOSSIL WOODS FROM THE MID-CRETACEOUS (ALBIAN) KACHAIKE FORMATION, SANTA CRUZ PROVINCE, ARGENTINA (Ameghiniana, 2023)
We describe 21 silicified woods from the Kachaike Formation (Albian, mid-Cretaceous), collected in the Tucu Tucu Ranch, west-central Santa Cruz Province, Argentinean Patagonia. The specimens are composed entirely of secondary xylem, and their preservation varies among them. Anatomical studies indicate that they are conifers related to the families Araucariaceae and Hirmeriellaceae (=Cheirolepidiaceae) and are placed into two fossil species: Agathoxylon antarcticum and Brachyoxylon patagonicum. All the specimens studied show marked growth rings, indicating annual seasonality. Decay patterns similar to those produced by modern xylophagous fungi are also recognized. The presence of Araucariaceae and Hirmeriellaceae fossil woods allows a better understanding of the paleoflora of the Kachaike  Formation, based previously only on palynological and fossil leaf studies. In addition, it provides additional information regarding conifers’ dominance of the tree canopy during the Cretaceous of Patagonia.